Evaluation of an ‘open box’ undergraduate laboratory experiment for understanding how a UV-Vis spectrometer works - Hirvioja, Sampo (My University, 2021)
In this study, a novel ‘open box’ spectrometer experiment that was introduced in a first-year undergraduate chemistry laboratory course in Durham University in 2018 was evaluated with the aim to determine its success and further improvement of the experiment. The learning objectives of the experiment and their alignment with it was examined. Furthermore, the impact of the open box nature of the experiment on students in understanding how a UV-Vis spectrometer works and how the assessment determines the level of students’ understanding was analysed. The focus group method was used as a research method. The focus groups involved developers and demonstrators of the experiment and four undergraduate students. Transcripts of the focus groups were analysed thematically to identify emerging themes. Findings from the focus groups suggested that the novel approach of the experiment was considered positive, but improvements are needed to make the experiment more efficient. The learning objectives were not completely achieved because they were not communicated properly to students. There was also too much content in the experiment. The open box nature was found to aid students’ understanding by enabling them to visualise the inside of a spectrometer, but the assessment should determine the level of students’ understanding more precisely.
Keywords: chemistry teaching, open box spectrometer, UV-Vis spectroscopy, first-year undergraduate, hands-on learning, laboratory experiment, learning objectives, formative assessment